Pengaruh Green Packaging Terhadap Keputusan Pembelian Ramah Lingkungan Produk Ajinomoto dengan Kesadaran Lingkungan Sebagai Variable Mediasi dalam Perspektif Bisnis Islam - Farhat Al Dura, Fati; Anggraeni, Erike; Restie Utamie, Zathu (Economic Reviews Journal, 2025)
This study aims to analyze the influence of green packaging on environmentally friendly purchase decisions of Ajinomoto products, with environmental awareness as a mediating variable in the perspective of Islamic business ethics. The research uses a quantitative approach with 100 respondents consisting of housewives in Bandar Lampung who have purchased Ajinomoto products with eco-friendly packaging. Data were collected using questionnaires and analyzed using SmartPLS 4. The results show that green packaging has a positive and significant effect on purchase decisions, green packaging has a positive and significant effect on environmental awareness, environmental awareness has a positive and significant effect on purchase decisions, and environmental awareness mediates the relationship between green packaging and purchase decisions. From an Islamic business perspective, the implementation of green packaging aligns with the principles of khalifah fil ardh (human stewardship of the earth) and mizan (balance), which encourage ethical, sustainable, and environmentally responsible consumption.